THE INFLUENCES OF TEACHING METHODOLOGIES TO THE STUDENTS’ GRADE POINT AVERAGE (GPA) OF ENGLISH DEPARTMENT OF UNIVERSITIES IN BATAM: ENGLISH DEPARTMENT OF UNIVERSITIES IN BATAM Eky Erlanda Edel, ekyedel@gmail.com, Universitas Putera Batam - Eky Erlanda Edel (BASIS (Bahasa dan Sastra Inggris), 2014)
This thesis is is aimed to find out the influences of teaching methodologie; learner roles and lecturer roles to the students’ Grade Point Average (GPA) in universities in Batam. It is important to analyze the teaching learning processes especially the teaching methods used by the lecturers. It is presumed that the effects of shift work system are becoming worse when the teaching methodologies used by the lecturer are not supported the students psychologically and physically. Thus, it is important to be understood by the lecturers that they are not teaching or lecturing the ordinary students which are workers and students at the same time. The subject of the study is the lecturers of English Department in Universities in Batam.